PENGARUH KARAKTERISTIK PEKERJAAN DAN KEDISIPLINAN TERHADAP KOMITMEN ORGANISASIONAL DENGAN DIMEDIASI OLEH KEPUASAN KERJA PEGAWAI (Studi Pegawai Politeknik Ilmu Pelayaran Semarang) - Sitepu, Firdaus (Students Journal of Economic and Management, 2012)
Target of this research to test work characteristic influence and discipline to organizational commitment with dimidiation by satisfaction work officer in is Politeknik Ilmu Pelayaran Semarang. Pursuant to the mentioned hence this research take title âPengaruh Karakteristik Pekerjaan Dan Kedisiplinan Terhadap Komitmen Organisasional Dengan Dimediasi Oleh Kepuasan Kerja PegawaiÂ  (Studi Pegawai Politeknik Ilmu Pelayaran Semarang)â. In this research take population in this research is Politeknik Ilmu Pelayaran Semarang amounting to 218 people. Intake of Sample with sampling random technique that is intake of sample at random counted 142 responder. Pursuant to result of research which have been conducted by hence can know by work characteristic have an effect on to satisfaction of job, discipline have an effect on to satisfaction of job, work characteristic have an effect on to organizational commitment, discipline have an effect on to organizational commitment and satisfaction of job have an effect on to organizational commitment. satisfaction of Job do not work characteristic medias and discipline to organizational commitment because indirect influence smaller than at direct influence. Keyword : Characteristic work, discipline, organizational commitment and satisfaction work